Do The Socio-Economic Status, Religious Attitudeand Customer Perception Impact On Customer Behavior? : Islamic Banking Case - Yuliaty, Tetty; Dalimunthe, Doli Muhammad Jafar; Hawariyuni, Weni (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to investigate customer behavior at Islamic banks,Indonesia. This research was analyzed by using path analysis approach involving 200 respondents as customers at several Islamic banks in Medan, Indonesia. Based on this research show the socio-economic status and religious attitudes have positively and significantly impactto customer behavior. On the other hand, socio-economic status and religious attitude are also positively and significantly impact for customer perceptions. Customer perceptions have the implication to increase positive customer behavior, sharia banking managers in Indonesia need to foster the religiosity of customers and target prospective customers who have good religiosity and good socio-economic status.